When time is of the essence: The use of rational emotive behavior therapy (REBT) informed single-session therapy (SST) to alleviate social and golf-specific anxiety, and improve wellbeing and performance, in amateur golfers. (May 2022) - Bowman, A.W.; Turner, M.J.
Abstract: Anxieties associated with the social evaluative nature of golf are present in the majority of athletes and impact directly on their wellbeing and objective performance. One potential intervention that could reduce social anxiety in golfers is rational emotive behavior therapy (REBT). There is limited research into the effectiveness of REBT in reducing social anxiety and even less research to assess if REBT can be delivered in time-constricted situations when the expectations for immediate results are high, as is the case with many handicap golfers. The current study used an idiographic single-case study design to assess the effects of REBT-informed single-session therapy (SST) on the social anxiety of five amateur golfers. REBT was employed in a short telephone call to target the performance issue, followed up with a single face-to-face session. Data were collected prior to, immediately following, and four weeks after the REBT intervention. Visual analysis following single-case guidelines revealed substantial reductions in irrational beliefs and social anxiety as well as improvements in wellbeing, scoring average, competition placings and handicap reductions in four out of five golfers. Discussion with golfers at a telephone follow-up indicated the positive receipt of REBT by the golfers and supported the visual analysis findings. This current study supports the effectiveness of REBT and also extends the research by demonstrating that REBT-informed SST can be an effective intervention, in a time-restricted environment, for those golfers with a clear target problem and who are ready to take care of business, providing clear implications for future research and practice. Highlights: Single-session Rational Emotive Behaviour Therapy (REBT) is proposed and tested with golfers. REBT brought about reductions in irrational beliefs and anxiety. REBT brought about increases in wellbeing and performance. Four out of five golfers reported positive effects, but one golfer did not.